Review of the Legality of Binary Options According to Islamic Law and Laws in Indonesia - Irkham Firdaus, Muhammad; Hisyam Hawari, Muhammadudy; Fathin Nur Ihsan, Muhammad (JURNAL RUANG HUKUM, 2022)
A binary Option is a financial or financial product in which the parties involved are placed on one of two options within a certain period of time. Juridically, the legality of Binary Options as a Futures Trading Commodity is still being debated. This is because in order to be considered a commodity, it must fulfill the phrase "future contract" as referred to in the Commodity Futures Trading Act. When referring to the objective terms of the contract, the contract must fulfill valid reasons where the Binary Option raises questions about the validity of the contract in the context of Binary Options. From a consumer perspective, without permission from CoFTRA for consumer protection, there is no clarity, both from a legal and practical perspective. The purpose of this study is to find out how Islamic law and laws in Indonesia treat the binary options affiliate system. Using normative law with a framework to find out legal norms, Islamic legal principles, and legal doctrines that are used to answer legal problems faced. take notes from literary books, laws, and regulations, newspapers, magazines, or online communication media that are relevant to the problem being studied